Strategi Promosi dan Penjualan di UMKM Karak Eco Bu Sum Perengsari Salatiga - Sukroni, Arif; Nur Nurlaili, Siti Alfiah; Putri Mahanani Riski, Astri Anindiya; Pawitrasari, Devita Tirta; Afidi, Anggi; Gulo, Eurasmus Hasrat; Asih, Listari; Setiawan, Setiawan; Utomo, Hardi (Universitas Pahlawan Tuanku Tambusai, 2025)
The emergence of the internet has made the development of digital technology skyrocket, allowing anyone to connect quickly throughout the world. Businesses such a MSMEs can take advantage of this technology to make better decisions, improve operational efficiency, and reach customers effectively. MSME Karak Eco Bu Sum located on Jl. Perengsari RT 8 RW 2, Kutowinangun Lor, Salatiga. is an MSME that produced karak crackers, along the way there are problems regarding business strategies such as promotion, sales and bookkeeping. The implementation of students in their community service through Community Empowerment Practice Lectures (KPPM) aims to develop MSMEs through learning, mediation and optimization of digital marketing. In an effort to increase sales reach, students accompany MSMEs interactively to create digital marketig accounts as a medium for promotion and sales, it’s a solution and innovation in business strategy in keeping up with developments in the digital world. The results of this activity show a significant increase in aspects of branding, operational efficiency, and broader marketing strategies.